2022
DOI: 10.1093/ajcn/nqab354
|View full text |Cite|
|
Sign up to set email alerts
|

Real ileal amino acid digestibility of pea protein compared to casein in healthy humans: a randomized trial

Abstract: Background It is necessary to propose plant alternatives to animal proteins that are of good nutritional quality. Pea is a good candidate owing to its high protein content and its well-balanced amino acid (AA) profile. Objectives This study aimed to assess the real ileal AA and nitrogen digestibility (RIDAA and RIDN) of pea protein isolate as compared to milk casein in humans. It also aimed to evaluate their nutritional quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 48 publications
2
23
0
Order By: Relevance
“…Overall, ileal digesta from humans are thus most preferred for assessment of protein quality. Some studies have indeed been conducted in humans to determine the ileal digestibility of proteins [ 64 , 65 , 66 ]. However, ileal digesta collection in human is complicated [ 67 ], and most data available to date on ileal digestibility of dietary proteins has come from animal models [ 68 ].…”
Section: Protein Quality Measurementmentioning
confidence: 99%
“…Overall, ileal digesta from humans are thus most preferred for assessment of protein quality. Some studies have indeed been conducted in humans to determine the ileal digestibility of proteins [ 64 , 65 , 66 ]. However, ileal digesta collection in human is complicated [ 67 ], and most data available to date on ileal digestibility of dietary proteins has come from animal models [ 68 ].…”
Section: Protein Quality Measurementmentioning
confidence: 99%
“…In addition, Guillin et al. (2022) demonstrated that the water solubility of chickpeas noticed a significant increase from 10.5% to 17% following a 24‐h fermentation process supported by LAB.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study by Gantumur et al (2023), the authors demonstrated that the solubility of proteins in water can increase from ∼89% to ∼95% by employing protein breakdown treatment using Saccharomyces cerevisiae yeast during fermentation. In addition, Guillin et al (2022) demonstrated that the water solubility of chickpeas noticed a significant increase from 10.5% to 17% following a 24-h fermentation process supported by LAB.…”
Section: Water Solubility Of Water Kefir-fermented Pea Proteinsmentioning
confidence: 97%
See 1 more Smart Citation
“…As an example, consuming pea protein isolate for16 weeks elicited similar digestibility, utilization, and effects on nitrogen balance as casein and whey in aged rats [ 10 ]. In healthy women and men receiving naso-ileal tube feedings, the digestibility and indispensable amino acid availability of pea protein extract was comparable to casein, with certain limitations for leucine, lysine, valine, and phenylalanine [ 11 ▪ ]. Similarly, 30 g milk protein ingestion resulted in quicker and overall greater increases in plasma leucine, lysine, methionine, and total amino acid concentrations over 5 h post ingestion, compared to ingesting 30 g potato-derived protein [ 12 ▪ ].…”
Section: Digestion and Absorption Of Animal And Plant Proteinmentioning
confidence: 99%